Tractor Stability for Agricultural Engineering Students: Learning Through a Project-Based Task - Castillo-Ruiz, Francisco J.; Arbizu-Milagro, Julia; Varela, Alejandro; Tascón, Alberto (International Journal of Engineering Pedagogy (iJEP), 2023)
Most of the fatalities in the agricultural sector in developed countries are related to machinery use, particularly tractor overturning. Despite its importance, a lack of practical teaching about this topic has been detected in the Agricultural Engineering curricula. For this reason, an active learning activity was planned within a teaching innovation project. The objective of this project was to design a structure as new teaching material to implement and use it to determine the tractor’s center of gravity coordinates. This teaching innovation project was organized in two stages: 1) The design of proposals by students following previously established requirements, and 2) A practical exercise to analyze tractor stability. Each stage involved students from two different Agricultural Engineering degree subjects. Before the second stage, the professor performed the final design of the structure based on previous proposals and later the structure was built. Five different ramp design proposals were received and graded in the first stage. A positive correlation between peer review and the professor’s grades was found. During the second stage, the ramps were used in another subject, in which the grades obtained in the related practical exercise were significantly higher in comparison with those got in the previous year. However, no improvement was found in the final exam grades. This activity involved students in the entire learning process and showed a positive influence on some of the evaluation activities.